Principalities and powers: revising John Howard Yoder’s sociological theology - Pitts, James Drake (The University of Edinburgh, 2011)
Evaluations of John Howard Yoder’s legacy have proliferated since his death in 1997. Although there is much disagreement, a broad consensus is forming that his theology was, on the one hand, focused on the social and political meaning of the New Testament accounts of Jesus Christ and, on the other hand, sociologically reductive, hermeneutically tendentious, and ecclesiologically ambiguous. This thesis proposes a revision of Yoder’s theology that maintains its broadly sociological emphasis but corrects for its apparent problems. In specific, adjustments are made to his social theory to open it to spiritual reality, to hone its analytical approach, and to clarify its political import. To do so his preferred framework for social criticism, the theology of the principalities and powers, is examined in the context of his wider work and its critics, and then synthesized with concepts from Pierre Bourdieu’s influential reflexive sociology. Yoder maintains that the powers, understood as social structures, are part of God’s good creation, fallen, and now being redeemed through their subjection to the risen Lord Christ. Bourdieu’s fundamental sociological concepts--habitus, capital, and field--enable an interpretation of the powers as dynamically constituted by their relations to the triune God and to personal dispositions. His treatment of social reproduction and freedom furthermore facilitate a construal of choice as a divinely gifted, sociologically mediated freedom for obedience to God. The sinful restriction of this freedom is read in light of Bourdieu’s concept of symbolic violence, which recognizes the ambiguity of violence without thereby identifying any form of killing as nonviolent. Violence and other phenomena can be investigated by a reflexive, dialogical, and empirically rigorous comparison with the life of Christ. The church’s spiritual participation in the redemption of the violent powers is conceptualized in Bourdieusian terms as a critical legitimation of other political and cultural fields made possible through autonomy from those fields. Christian social distinctiveness moreover has universal meaning because it is oriented towards the worship of God and so radically welcoming of others; and this sociological universality is distinctive because it is the result of a particular history of social struggles with and for God. These revisions to Yoder’s theology of the principalities and powers produce a sociological theology that is material and spiritual, critical and dialogical, and particular and universal. By incorporating these revisions, Yoder’s work can continue to support those who seek peace in a world riven by violence.
Keywords: theology; sociology; Yoder, John Howard; Bourdieu, Pierre